2019
DOI: 10.1183/13993003.02435-2018
|View full text |Cite
|
Sign up to set email alerts
|

A simple echocardiographic estimate of right ventricular-arterial coupling to assess severity and outcome in pulmonary hypertension on chronic lung disease

Abstract: A simple echocardiographic estimate of right ventricular-arterial coupling to assess severity and outcome in pulmonary hypertension on chronic lung diseaseTo the Editor:The adaptation of right ventricular (RV) systolic function to afterload is a major determinant of outcome in pulmonary hypertension [1]. The gold standard measurement of RV-pulmonary arterial (PA) coupling is the ratio of end-systolic to arterial elastances (E es /E a ) which is optimal for RV flow output at minimal energy cost at values betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…TAPSE/PASP is a reproducible marker for right ventricular-arterial coupling which is a well-known predictor of mortality in PH. 12 15 We suggest that including right ventricular-arterial coupling mirrored by TAPSE/PASP increases the reliability of the presented method. Both 6MWD and TAPSE/PASP are non-invasive parameters that can be determined easily.…”
Section: Discussionmentioning
confidence: 92%
“…TAPSE/PASP is a reproducible marker for right ventricular-arterial coupling which is a well-known predictor of mortality in PH. 12 15 We suggest that including right ventricular-arterial coupling mirrored by TAPSE/PASP increases the reliability of the presented method. Both 6MWD and TAPSE/PASP are non-invasive parameters that can be determined easily.…”
Section: Discussionmentioning
confidence: 92%
“…Subsequent studies con rmed its prognostic capability, not only in heart failure (21) but also in pulmonary arterial hypertension (22) and in patients with chronic lung diseases (23). In these studies, the TAPSE/PASP was assumed to inform about RV-PA coupling, with TAPSE considered as a load-dependent surrogate of Ees and PASP as an indirect estimate of Ea (21)(22)(23). The TAPSE/PASP has been shown to be superior to other composite echocardiographic indices in the assessment of RV-PA and correlated to gold standard invasive (11) or indirectly assessed Ees/Ea ratios.…”
Section: Discussionmentioning
confidence: 96%
“…The TAPSE/PASP ratio was initially proposed as an estimate of RV myocardial length-tension relationship, and as such showed to be of prognostic relevance in heart failure (20). Subsequent studies con rmed its prognostic capability, not only in heart failure (21) but also in pulmonary arterial hypertension (22) and in patients with chronic lung diseases (23). In these studies, the TAPSE/PASP was assumed to inform about RV-PA coupling, with TAPSE considered as a load-dependent surrogate of Ees and PASP as an indirect estimate of Ea (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The TAPSE/PASP ratio was initially proposed as an estimate of RV myocardial length-tension relationship and as such showed to be of prognostic relevance in heart failure [21]. Subsequent studies confirmed its prognostic capability, not only in heart failure [22] but also in pulmonary arterial hypertension [23] and in patients with chronic lung diseases [24]. In these studies, the TAPSE/PASP was assumed to inform about RV-PA coupling, with TAPSE considered as a loaddependent surrogate of Ees and PASP as an indirect estimate of Ea [22][23][24].…”
Section: Discussionmentioning
confidence: 97%